The Impact Of War On Syrian Arab Republic In Some Indicators Of Foreign Trade - عصام اسماعيل; يونس احمد ديب (Latakia University Journal - Economic and Legal Sciences Series, 2022)
At the beginning of 2011, Syria was exposed to an unconventional war aimed at destroying all aspects of economic, social and political life. In this context, Syria has always been preparing for this situation by directing all available energies and resources to be able to confront and win any war it is waging in the future. The objective of the research was to study the impact of the war and the significant changes that accompanied it in the functioning and structure of economic variables in Syria and to compare the situation of certain foreign trade indicators in the period of pre-war economic reform and wartime. The study was conducted using the analytical descriptive method to study and analyze the situation of the foreign trade sector in Syria during the period before the war (2000-2010) and the war period (2011-2019), using two indicators of economic exposure and import penetration during the period in question. The researcher found a relationship between the economic changes that accompanied the war and the deterioration of the value of the economic exposure index. Moreover, he found a relationship between the economic changes that accompanied the war and the deterioration of the value of the import penetration index. The researcher recommended continuing to implement the policy of import legalization and working to launch strategic projects that provide the necessary infrastructure for the reconstruction process, thereby This helps the economy recover as quickly as possible, in addition to working to raise the rate of self-sufficiency and direct financing to the economic sectors that are most important.